Translation Techniques for Imperative Sentences and Meaning Shifts in the Translation of the Book “‘Izhotun Nāsyiīn” by Musthafa Al-Ghalayain: Teknik Penerjemahan Kalimat Imperatif dan Pergeseran Makna Pada Terjemah Kitab “‘Izhotun Nāsyiīn” Karya Musthafa Al-Ghalayain - Inayati, Nailul (Kementerian Sekretariat Negara Republik Indonesia, 2025)
In the translation of the book “‘Izhotun Nāsyiīn”, there are differences in meaning between the singular imperative verb and when combined with other words. Translators use certain techniques to translate these words to produce an understandable translation for readers and consistent translation with the author's intention. The researcher conducts research on the techniques used in translating imperative sentences in the book “‘Izhotun Nāsyiīn” and the effect of their use on the shift in meaning based on the theories of Molina and Albir. This research uses a qualitative descriptive method. The translator uses 11 techniques in translating 112 imperative sentences in the book “‘Izhotun Nāsyiīn”, namely literal translation, linguistic amplification, adaptation, modulation, description, substitution, amplification, generalization, common equivalence, compensation, and reduction. Of the 112 imperative sentences translated using Molina and Albir's translation techniques, there are 60 imperative sentences that have shifted its meaning from the original one. This was taken by the translator to make understandable translation for readers and ensure the author’s intended message is well-conveyed. The contribution of this research to the field of translation, particularly the translation of Arabic texts into Indonesian, is that the translation of Arabic religious texts cannot be carried out through literal translation alone, but also requires more flexible translation techniques so that the information can be conveyed properly.